Early tumour size changes from neoadjuvant chemotherapy as a predictor of pathologic response in breast cancer - Erika Z. Chung; David Alberico; Lakshmanan Sannachi; Archya Dasgupta; Joyce Yip; Maria Lourdes Anzola Pena; Sonal Gandhi; Belinda Curpen; Gregory J. Czarnota (PLoS ONE, 2026)
Neoadjuvant chemotherapy (NAC) is the standard of care for locally advanced, human epidermal growth factor receptor 2-positive, and triple negative breast cancer. While complete pathologic response is associated with improved outcomes, NAC response varies and is only assessed post-surgery. Identifying response earlier can allow for timely treatment personalization, reducing toxicity and costs as well as improving efficacy. This study aimed to assess the feasibility of using early changes in tumour size, as measured by ultrasound during chemotherapy at 6 times, to predict final pathological response to NAC in breast cancer patients. Eligible participants were ≥18 years with biopsy-proven stage l-lll breast cancer who received standard NAC and underwent ultrasound imaging at weeks 0, 1, 4, 8, 12, and 16 during chemotherapy. A modified response grading system based on post-operative histopathological evaluation was used to classify patients as Complete Responders (CR), Partial Responders (PR), Weak Responders (WR), or Non-Responders (NR). Changes in tumour diameter, area, and volume were evaluated as early predictors of final pathologic response. Statistical analysis was performed to assess changes from baseline to each time point across pairs of groups. A total of 106 patients were included. Post-NAC response rates were assessed for each group. CRs displayed steep reductions in diameter, area, and volume in the early weeks of NAC, while PRs showed more consistent and moderate decreases. WRs demonstrated less pronounced reductions, and NRs remained largely unchanged across all time points. Statistical analysis confirmed differences in tumour size changes between CRs and other groups (p < 0.05), supporting the observed trends in diameter, area, and volume reductions. Overall, early changes in tumour size may provide some predictive value for final pathologic response to NAC but are likely insufficient on their own, underscoring the need for more robust predictive markers.